2022
DOI: 10.1080/02602938.2022.2048355
|View full text |Cite
|
Sign up to set email alerts
|

Contradicting findings of gender bias in teaching evaluations: evidence from two experiments in Denmark

Abstract: A series of studies have found gender bias in student evaluations of teaching. Evidence from several observational studies show that women are evaluated lower than men. These findings are supported by experimental studies aimed at isolating the effect of a possible gender bias from other differences between male and female teachers. In this paper, we conduct two experiments in Denmark to test whether a similar gender bias is present in a national context that is generally considered among the most gender equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A study of more than 500,000 evaluations at an Australian university found divergence across different academic disciplines, indicating that the presence of female role models may matter for gender differences (Fan et al, 2019). Experimental evidence from Denmark also suggests that findings of gender bias may not necessarily be replicable across different contexts (Binderkrantz et al, 2022). Finally, two studies of evaluations at a US university and a university in Brazil did not identify systematic gender differences-but it is notable that the study designs did not include the gender of students (Arrona-Palacios et al, 2020;Zipser et al, 2021).…”
Section: Literature Review: Gender Bias and Gender Affinity Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of more than 500,000 evaluations at an Australian university found divergence across different academic disciplines, indicating that the presence of female role models may matter for gender differences (Fan et al, 2019). Experimental evidence from Denmark also suggests that findings of gender bias may not necessarily be replicable across different contexts (Binderkrantz et al, 2022). Finally, two studies of evaluations at a US university and a university in Brazil did not identify systematic gender differences-but it is notable that the study designs did not include the gender of students (Arrona-Palacios et al, 2020;Zipser et al, 2021).…”
Section: Literature Review: Gender Bias and Gender Affinity Effectsmentioning
confidence: 99%
“…1 Denmark is a society with a high level of educational gender equality and relatively widespread support for egalitarian gender norms-even though women remain underrepresented at the higher academic ranks (Boehnke, 2011;World Economic Forum, 2021;Nielsen, 2017). Moreover, in recent experimental studies of teaching evaluations in Denmark, no gender difference in SETs was found (Binderkrantz et al, 2022). We combine three different data sources to analyze: (1) whether there is a gender difference in actual teaching evaluations, (2) possible gendered patterns in the comments provided by students in teaching evaluations, and (3) student experiences with teachers of different gender as expressed in interviews.…”
Section: Introductionmentioning
confidence: 99%